The pancaking of coronal mass ejections: an in situ attestation - Shaikh, Zubair Ibrahim (My University, 2020)
The interplanetary counterparts of coronal mass ejections (ICMEs) are the leading driver of severe space weather. Their morphological evolution in interplanetary space and the prediction of their arrival time at Earth are the ultimate focus of space weather studies, because of their scientific and technological effects. Several investigations in the last couple of decades have assumed that ICMEs have a circular cross-section. Moreover, various models have also been developed to understand the morphology of ICMEs based on their deformed cross-section. In fact, simulation studies have suggested that the initial circular cross-section flattens significantly during their propagation in the solar wind and this is referred to as ‘pancaking’. However, an observational verification of this phenmenon is still pending and it will eventually be the primary concern of several morphological models. Here, we report the first unambiguous observational evidence of extreme flattening of the cross-section of ICMEs, similar to pancaking, based on in situ measurements of 30 ICME events. In fact, we conclude that the cross-section of ICME flux ropes transformed into a two-dimensional planar magnetic structure. Such a deformed morphological feature not only alters the prediction of their arrival time but also has significant implications in solar-terrestrial physics, the energy budget of the heliosphere, charged particle energization, turbulence dissipation and enhanced geo-effectiveness, etc.
Keywords: CME, Coronal mass ejection